2010
DOI: 10.1051/0004-6361/200912500
|View full text |Cite
|
Sign up to set email alerts
|

The instability transition for the restricted 3-body problem

Abstract: Aims. We present a new method that allows identifying the onset of orbital instability, as well as quasi-periodicity and multiperiodicity, for planets in binary systems. This method is given for the special case of the circular restricted 3-body problem (CR3BP). Methods. Our method relies on an approach given by differential geometry that analyzes the curvature of the planetary orbit in the synodic coordinate system. The centerpiece of the method consists in inspecting the effective (instantaneous) eccentricit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Comparisons to previously established criteria for stability show that our results are consistent with previously obtained stability limits (e.g., Holman & Wiegert 1999;Musielak et al 2005;Cuntz et al 2007;Eberle et al 2008;Eberle & Cuntz 2010). In Eberle et al (2008), Paper I, the onset of instability was related to the topology of the ZVC, whereas in Eberle & Cuntz (2010), Paper II, it was shown that the onset of orbital instability occurs when the median of the effective eccentricity distribution exceeds unity.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Comparisons to previously established criteria for stability show that our results are consistent with previously obtained stability limits (e.g., Holman & Wiegert 1999;Musielak et al 2005;Cuntz et al 2007;Eberle et al 2008;Eberle & Cuntz 2010). In Eberle et al (2008), Paper I, the onset of instability was related to the topology of the ZVC, whereas in Eberle & Cuntz (2010), Paper II, it was shown that the onset of orbital instability occurs when the median of the effective eccentricity distribution exceeds unity.…”
Section: Discussionsupporting
confidence: 91%
“…Using the method of Lyapunov exponents, we are able to verify and extend the methods described by Eberle et al (2008) and Eberle & Cuntz (2010). Absolute orbital stability can be more rigorously shown through the Lyapunov exponent method.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations